2021
DOI: 10.1242/bio.058600
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A cycle byproducts explain retinal damage and molecular changes thought to initiate retinal degeneration

Abstract: In the most prevalent retinal diseases, including Stargardt disease and age-related macular degeneration (AMD), byproducts of vitamin A form in the retina abnormally during the vitamin A cycle. Despite evidence of their toxicity, whether these vitamin A cycle byproducts contribute to retinal disease, are symptoms, beneficial, or benign has been debated. We delivered a representative vitamin A byproduct, A2E, to the rat's retina and monitored electrophysiological, histological, proteomic, and transcriptomic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…The RPE lipofuscin contains about 20 different bisretinoid fluorophores-byproducts of the visual cycle. A2E is one of the most well-studied by-products of the vitamin A cycle [21]. When exposed to light, A2E undergoes photooxidative destruction, which results in the formation of oxidized products containing amphiphilic and hydrophilic molecules.…”
Section: Formation Of Water-soluble Carbonyl Products During Photooxi...mentioning
confidence: 99%
See 2 more Smart Citations
“…The RPE lipofuscin contains about 20 different bisretinoid fluorophores-byproducts of the visual cycle. A2E is one of the most well-studied by-products of the vitamin A cycle [21]. When exposed to light, A2E undergoes photooxidative destruction, which results in the formation of oxidized products containing amphiphilic and hydrophilic molecules.…”
Section: Formation Of Water-soluble Carbonyl Products During Photooxi...mentioning
confidence: 99%
“…A2E and its oxidation products accumulated by RPE cells are apparently implicated in the pathogenesis of several retinal degenerative diseases such as Best macular dystrophy, Stargardt-like macular dystrophy, Stargardt disease, and age-related macular degeneration (AMD) [16][17][18][19][20]. Therefore, it has been hypothesized that the atrophic lesions observed in retinal diseases such as Stargardt disease and AMD can be the result of poisoning due to the chronic formation of visual byproducts-in particular, A2E [21]. It was shown that A2E is capable of damaging RPE cells, the outer and inner segments of photoreceptors, and cells of the outer plexiform layer of the retina; cause the formation of sub-retinal debris; alter transcription; and diminish retinal function [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particular genotypes are associated with AMD, and as in STGD, ABCA4 has been specifically implicated ( 204 , 205 ). Accumulation of bisretinoids such as A2E is associated with AMD as well as STGD, and administration of exogenous A2E induces ocular changes similar to AMD and STGD in animal models ( 206 208 ). However, defining a causal link between ABCA4 mutations and AMD has proven more challenging, as some researchers find no association ( 209 , 210 ), perhaps due to genetic heterogeneity in the AMD phenotype, or incomplete penetrance of disease-causing alleles ( 211 ).…”
Section: Parainflammatory Degenerative Retinal Diseasementioning
confidence: 99%
“…As the retina is exposed to physiological stress, immune activation may exacerbate cellular damage, leading to loss of function ( 214 ). In Stargardt disease, the A2E vitamin A cycle byproducts form abnormally in the young retina, whereas in AMD, the byproducts form, to a similar degree, in the aged retina and it is hypothesised that the difference in the two diseases is explained by the age of the eye in which the vitamin A cycle byproducts ( 208 ). Determining the effects of dietary vitamin A on parainflammation in STGD1 and AMD is complex as it requires consideration of the pleotrophic effects of RA-signalling and its targets (in the eye, gut or other immunological sites), the age of the eye, the extent of local retinal disease, as well systemic immunological factors.…”
Section: Parainflammatory Degenerative Retinal Diseasementioning
confidence: 99%